Native American landmarks and festivals a traveler's guide to Indigenous United States and Canada - Dennis, Yvonne Wakim; Hirschfelder, Arlene B. (Visible Ink Press, 2019)
"Descriptions and information about Native American festivals, museums, and other points of interest in the United States and Canada"--
Keywords: Indian tourism / United States; Indian tourism / Canada; HISTORY / United States / State & Local / General; Indian tourism; Canada; United States; Guidebook; Electronic books; travel guidebooks; Guidebooks; Guides touristiques